FREUD AND THE FILIPINO YOUTH: REVISITING FREUD’S THEORY ON GENDER, SEX, AND LOVE - DOCTOR, JINAMARLYN B. (International Journal of Psychosocial Rehabilitation, 2020)
Freud’s theory on gender, sex and love has been constantly viewed as a relevant topic in social science and education spheres. As there are many aspects in this theory that need to be investigated because of the ever changing social landscape, this paper revisits the views of selected college students on specified constructs of the theory. It tried to discover significant findings from the philosophy of Freud to understand whether his concepts are resonated through the perspectives of selected college students. By means of Interpretative Phenomenological Analysis (IPA), a qualitative approach exploring the lived experience of the participants. The study discovered that Freud’s knowledge on sexuality is still manifested by both Filipino male and female sexes. This was revealed by comparing how Filipino male and female fall in love in this day and age. Based on the results, the college students described Filipino male as passive, much faster in being aware of their sexuality, wild and harsh, responsible, hard-working and a good provider in the family; while women are conservative, powerful than before, and surprisingly no tradition exists for them. Moreover, the students claim that male and female differ in how they express their love such as male cry but it is usually hidden, showing sincerity, and honesty. On the other hand, female are too expressive and emotional; expresses love by kissing, hugging, etc. In this study, the role of society is very vital in establishing sexuality.